Le Djebel Nefousa. Transcription, traduction française et notes avec une étude grammaticale - Calassanti Motylinski, Adolphe de (Leroux, 1898)
Composed by Brahim ben Sliman Chemmakhi, Ṭālib from Īfren, 16 Ramaḍān 1302/1885. In the notes references to Shammākhī’s Siyar.
Keywords: Linguistique – Djebel Nefousa

Le Djebel Nefousa (Ir’asra d’ibriden di drar n infousen). Relation en Temazir’t de Djebel Nefousa, composée par Brahim ou Slimane Chemmakhi, taleb d’Ifren - Shammākhī, Ibrāhīm Sulaymān (Adolphe Jourdan, 1895)
Keywords: Linguistique – Djebel Nefousa; Récits de voyage – Djebel Nefousa

Dyebayli Vocabulary, from an Unpublished MS. A.D. 1831 - Grimal de Guiraudon, Th. (Journal of the Royal Asiatic Society of Great Britain and Ireland, 1893)
About the middle of the year 1887, having bought from Dr. R. N. Cust a lot of books and papers relating to the African languages, I found amongst them a Gebilee and Bornoo manuscript Vocabulary, very carefully written on three double sheets of rough paper : on examining it, the Gebilee proved at once to be a Berber dialect, spoken in the mountainous region lying about 50 miles S. of Tripoli, and extending 150 miles in a direction from W.SW. to E.NE. However, inasmuch as I was then engaged in another part of Africa, I had not at first attached much importance to this document; but, later on, having sent it for inspection to Prof. Ren? Basset, of Algiers, this eminent scholar urged on me the necessity of publishing my manuscript, the peculiar dialect to which it refers having not yet been illustrated ; at the same time, he sent me some valuable Notes, which have greatly helped me to extricate myself amongst many inaccuracies
Keywords: Linguistique – Djebel Nefousa